Analisis Stabilitas Lereng Tumpukan Gipsum Menggunakan Metode Hitungan Manual (Fellenius) - Aradhana Afif Taqwanto; Akhmad Andi Saputra; Ikhtisholiyah Ikhtisholiyah; Dandy Nugroho (Jurnal Kridatama Sains dan Teknologi, 2026)
The stability of gypsum stockpile slopes is critical to ensuring occupational safety, operational continuity, and the security of industrial facilities. The stability of gypsum stockpiles is governed by the slope geometry and the geotechnical properties of the material, particularly its unit weight, cohesion, and internal friction angle. This study aims to evaluate the stability of a gypsum stockpile slope at PT X's storage area using the Fellenius method (Ordinary Method of Slices). A quantitative approach was employed through field measurements of slope geometry and the collection of geotechnical parameters from the company's technical data. The analysis was performed under drained conditions by assuming a circular slip surface and neglecting interslice forces in accordance with the fundamental assumptions of the Fellenius method. The potential sliding mass was divided into seven vertical slices to determine the ratio between resisting and driving forces, from which the Factor of Safety (FoS) was calculated. The analysis yielded a Factor of Safety of 1.98, indicating that the gypsum stockpile slope is stable and meets the accepted slope-stability criteria. The results demonstrate that the combination of slope geometry and the shear strength parameters of the gypsum material provides sufficient resistance to overcome the driving forces acting along the potential failure surface. This study contributes to the application of the manual Fellenius method for evaluating the stability of gypsum stockpiles under drained conditions and provides a preliminary reference for assessing the slope stability of gypsum stockpiles in industrial environments, as well as for future studies employing other limit equilibrium methods.